Antibiotic Prophylaxis for Cesarean Delivery: A Survey of Anesthesiologists. (16th December 2020) - Reiff, Emily S.; Habib, Ashraf S.; Carvalho, Brendan; Raghunathan, Karthik
Abstract : Background . The most common complication after cesarean delivery is surgical site infection. Antibiotic prophylaxis reduces infectious morbidity and current anesthetic quality metrics include preincision antibiotic prophylaxis. Recently, studies suggest reductions in infectious morbidity with the addition of azithromycin for unscheduled cesarean delivery. Larger doses of cefazolin are recommended for morbidly obese women, but evidence is conflicting. The aim of this study was to survey anesthesiologists to assess current practice for antibiotic prophylaxis for cesarean delivery. Methods . We invited a random sample of 10, 000 current members of the American Society of Anesthesiologists to complete an online survey about their current practice of antibiotic prophylaxis for cesarean delivery in November 2017. The survey included questions similar to a previous survey on this topic in 2012. Results . The response rate was 12.2% ( n  = 1223). Most respondents had at least 15 years of experience (684, 55.9%), work at a nonteaching or community hospital (729, 59.6%), with >500 cesarean deliveries annually (619, 50.6%), and administer obstetric anesthesia several times a week (690, 56.4%). Routine preincision antibiotic prophylaxis was reported by 1162 (95.0%) of the 1223 respondents, a substantial improvement versus the 63.5% reported in the previous study in 2012. For intrapartum cesarean deliveries, 141 (11.5%) administer azithromycin for unscheduled cesarean deliveries. Those who use cefazolin, 509 (42.5%) administer 3 g for morbidly obese women. Conclusion . Adherence to preincision antibiotic prophylaxis for cesarean delivery is very high, a significant improvement within 5 years. A minority of anesthesiologists utilize azithromycin for intrapartum cesarean deliveries. The dose of cefazolin for morbidly obese women varies widely.